On Farm Research Is a Viable Means of Technology Verification, Dissemination And Adoption: A Case of Wheat Research in Nepal - Timsina, K P; Gairhe, S; Magar, DB Thapa; Ghimire, Y N; Gauchan, D; Padhyoti, Y (Agronomy Journal of Nepal, 2016)
A study on the role of on-farm/outreach research (OR) site in wheat technology dissemination was conducted in Terai regions of Sunsari, Rupandehi and Banke districts, Nepal. On-farm research sites representing irrigated, partially irrigated and rainfed production domains and their comparative control, the non-outreach research sites were selected. From the list of wheat growers in respective study sites, 30 samples from each of the VDCs were selected randomly irrespective of their landholdings with the total sample size of 180 for the study. The study revealed that overall area covered by the improved varieties was about 94%; however, it was 100 % in OR site. The area covered by the improved varieties released after 1990s was found higher in OR site but there was still domination of improved variety Nepal 297 in the study area, which was released in 1985. The Technological Adoption Index (TAI) for wheat was found higher (0.63) in OR site compared to non-OR site (0.43). Test for equality of mean of TAI was carried out between OR and non-OR sites and found significantly different (P=<0.000) between the sites. Farmers were categorized into low adopters, medium adopters and high adopters based on their TAI value after conversion into percentage. Chi-square test shows the significance difference (χ2 =24.82 and P=<0.000) in number of farmers in different adoption categories between OR and non-OR sites. Results indicate OR sites are playing viable role for increasing number of high adopters (farmers) compared to non-OR site farmers. The knowledge on good agriculture management, access to modern improved seed, and use and availability of agriculture information, availability of agricultural inputs and loan were found significantly high on OR sites. There exists large scope for yield improvement of the wheat in Nepal by increasing number of outreach sites and by strengthening institutional coordination and linkage among the related stakeholders at different levels to provide system based packages rather than component technology for mass dissemination and adoption of technology among the farmers at large. Agronomy Journal of Nepal (Agron JN) vol. 4, 2016, page: 9-24